2018
DOI: 10.1111/ddi.12690
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of defence and performance traits between one widespread clone and native populations in a major invasive plant species

Abstract: Aim The success of invasive species in their introduced range is often assumed to result from evolutionary changes in defence and growth traits, or as a response to more favourable conditions. The latter is assumed particularly for species exhibiting low, or even no, sexual reproduction in the introduced range. Location and Methods Here, we compared Japanese (native range) and French (introduced range) populations of Fallopia japonica under common growth conditions in a glasshouse. We measured height, abovegro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…Additionally, in North America invasion of diverse habitats by few Japanese knotweed genotypes has been correlated with epigenetic differentiation, with the conclusion that some epigenetic loci may respond to local microhabitat conditions [ 23 ]. Japanese knotweed from different sources grown in the same greenhouse have been known to possess differing levels of physiological vigour, with the French variant growing more vigorously than its Japanese counterpart, suggesting either a rapid evolution or pre-adaptation [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in North America invasion of diverse habitats by few Japanese knotweed genotypes has been correlated with epigenetic differentiation, with the conclusion that some epigenetic loci may respond to local microhabitat conditions [ 23 ]. Japanese knotweed from different sources grown in the same greenhouse have been known to possess differing levels of physiological vigour, with the French variant growing more vigorously than its Japanese counterpart, suggesting either a rapid evolution or pre-adaptation [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…No difference or even higher resistance of invasive populations are also found in other invasive species within common garden experiment, for example, in Chromolaena odorata (Liao et al, 2014), Brassica nigra (Oduor et al, 2011), and in Verbascum Thapsus (Endriss et al, 2018). Similar or higher resistance and performance of introduced Japanese populations of R. japonica was also documented by Rouifed et al (2018), in which they found that introduced populations did not differ in composition of secondary metabolites, stem stiffness, leaf thickness, aboveground biomass and height, but were higher in leaf toughness and belowground biomass to the native R. japonica populations when grown under similar condition in the introduced range. As the Japanese populations used in our experiments were likely from the source region of the introduced European and North American populations, our results thus provide evidence that the introduction of certain genotypes (i.e.…”
Section: Differences In Herbivore Resistance Among Rangesmentioning
confidence: 81%
“…It compared only five native Japanese and five invasive French populations in a common garden in the introduced range, but it also found that introduced populations did not differ in their composition of secondary metabolites, stem stiffness and leaf thickness, but that they had even higher leaf toughness than native Japanese populations. As the Japanese populations used in our experiments – as well as those used in Rouifed et al . (2018) – were from the putative source region of knotweed introductions to Europe and North America, our results thus indicate that the introduction of plants with particular resistance profiles, rather than post-invasion evolution, underlies the trait divergence between the native and introduced range, and may have played a role in the invasion success of R. japonica .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations